2009
DOI: 10.1016/j.joca.2009.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of calcium-containing crystals to cartilage degradation and synovial inflammation in osteoarthritis

Abstract: Crystals extracted from human osteoarthritic knee cartilage induce the production of proinflammatory and catabolic mediators (NO, MMP-13 and PGE(2)) in human primary chondrocytes and synoviocytes. Synthetic calcium phosphate and pyrophosphate crystals elicit a similar response in those cells. Our findings suggest that these crystals could contribute to cartilage degradation and synovitis in OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 50 publications
1
29
1
3
Order By: Relevance
“…This hypothesis is further supported by Fuerst and colleagues' findings that chondrocytes isolated from mineralized OA cartilage could undergo hypertrophic differentiation and might ultimately produce BCPs. However, as recently described by Liu et al (10), and as we have also observed, isolation of chondrocytes from a crystalcontaining articular cartilage leads to crystal release in the culture medium, so that the distinction between crystals released from the matrix and newly produced crystals is difficult to ascertain.…”
Section: To the Editormentioning
confidence: 48%
“…This hypothesis is further supported by Fuerst and colleagues' findings that chondrocytes isolated from mineralized OA cartilage could undergo hypertrophic differentiation and might ultimately produce BCPs. However, as recently described by Liu et al (10), and as we have also observed, isolation of chondrocytes from a crystalcontaining articular cartilage leads to crystal release in the culture medium, so that the distinction between crystals released from the matrix and newly produced crystals is difficult to ascertain.…”
Section: To the Editormentioning
confidence: 48%
“…Fist, calcium deposition has been shown to play a significant role in OA pathology, including the articular cartilage [36][37][38]. Calcium deposition has been shown to lesson actual mechanical efficacy of the articular cartilage and associated menisci [38].…”
Section: Discussionmentioning
confidence: 99%
“…Basic calcium phosphate (BCP) and calcium pyrophosphate dihydrate (CPPD) crystals are commonly found in osteoarthritic joints. These crystals have been found in the synovial fluid of 60% of patients with knee OA and over 90% of a small group of patients with grade-4 OA [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The rationale using colchicine as disease/ structure-modifying drug to manage OA resides in the fact that calcium-containing crystals are frequently seen in OA (3,4), and colchicine has been shown to be beneficial in preventing calcium crystal-induced inflammation (pseudogout). When used to treat gouty arthritis, colchicine is believed to work by inhibiting microtubule dependent cell infiltration and IL-1β production.…”
Section: Introductionmentioning
confidence: 99%